Errors in epicenter locatins at the Institute of Seismology, University of Helsinki - Hanski, Ida-Maria (Helsingin yliopisto, 2025)
We have here in Finland very few earthquakes because of Finland`s location (Fennoscandian shield). It can be said,that natural seismicity in Finland is low. About 18 000 seismic events are reported in Finland annually. Only 1-2 % are classified as earthquakes. Most events are classified as constructions or mine explosions. Starting from year 1961 The Institute of Seismology University of Helsinki (ISUH) has taken responsibility for seismic monitoring in Finland. There are close 50 seismic stations in Finland, which give comprehensive observations about seismic events. There has been an interest to find out how large are the location errors when measuring earthquakes, when measurement is done both automatically and manually. Because we have only few earthquakes, this can be explored by using explosions. There can be many errors in locating explosions. I choose this topic, because it seems interesting and I want to know if there are differences when using automatic or manual method and how large these differences are. In this work we studied the location errors of events and where the errors are coming from. ISUH collects ground truth data: time, coordinates and the number of explosions from mines and quarries. Hukkakero, Vuosaari, Kevitsa and Parainen explosion sites were included in the research. The explosions were made during 2020–2022. In Hukkakero, automatic and manual detection recognized 23 events. In Kevitsa, there were automatically recognized 35 and manually 43 events. In Vuosaari, there were automatically recognized 179 and manually 119 events. Parainen was not mentioned in results, because there were only two events. In Hukkakero using the manual location method the measurement error is smaller than with automatic measurement. In Kevitsa error measured with manual methods is half smaller than the automatically measured one. In Vuosaari the difference between these two methods is not significant. Location errors may depend on errors in picking and identifying of phases, the number of stations, the ...